Nutritional and lipid profiles of the dorsal and ventral muscles of wild pirarucu - Amaringo Cortegano, Carlos Andre Andre; Godoy, Leandro Cesar de; Petenuci, Maria Eugênia; Visentainer, Jesuí Vergílio; Affonso, Elizabeth Gusmão; Gonçalves, Ligia Uribe (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to analyze the proximate and fatty acid composition of the dorsal and ventral muscles of wild pirarucu (Arapaima gigas) captured from a Brazilian Amazonian lake. Dorsal and ventral muscles were dissected out, freeze-dried, vacuum-packed, and had the proximate and fatty acid composition analyzed. Ash, total proteins, and lipids were inversely proportional to moisture and had higher levels in the ventral muscles. Twenty-seven fatty acids were quantified in both muscles without significant differences between them, except for the heneicosylic, palmitoleic, γ-linolenic, and dihomo-γ-linolenic acids. Saturated and monounsaturated fatty acids were predominant in both muscles. The eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids were quantitatively similar: 9.25 (dorsal) to 10.14 (ventral) and 8.50 (dorsal) to 10.63 (ventral) mg g-1 of total lipids, respectively. The EPA+DHA content of the dorsal and ventral muscles were 113.25 and 165.78 mg 100 g-1, respectively. The ratios of polyunsaturated/saturated (0.54 and 0.59 for the dorsal and ventral muscles, respectively), n-3/n-6 (0.20 and 0.21), and hypocholesterolemic/hypercholesterolemic fatty acids (1.41 and 1.45) ratios, as well as the atherogenicity (0.59 and 0.53) and thrombogenicity (1.02 and 0.94) indices, indicate that pirarucu muscle is a good dietary source of EPA+DHA, and its nutritional lipid quality can be beneficial for human health.